Effect of 7, 8-dihydroneopterin mediated CD36 down regulation and oxidant scavenging on oxidised low-density lipoprotein induced cell death in human macrophages. (June 2017) - Shchepetkina, Anastasia A.; Hock, Barry D.; Miller, Allison; Kennedy, Martin A.; Gieseg, Steven P.
Abstract: The role of CD36 in oxidised low-density lipoprotein (oxLDL) mediated cell death was examined by down regulating the receptor level with the macrophage generated antioxidant 7, 8‐dihydroneopterin. Down regulation of CD36 protein levels in human monocyte derived macrophages by 7, 8-dihydroneopterin corresponded to a decrease in CD36-mRNA. The oxidation products of 7, 8-dihydroneopterin, dihydroxanthopterin and neopterin did not significantly down regulate CD36. The CD36 down regulation resulted in a decrease in oxLDL uptake measured as 7-ketocholesterol accumulation. Though less oxLDL was taken up by the macrophages as a result of the 7, 8-dihydroneopterin induced down regulation in CD36 levels, the cytotoxicity of the oxLDL was not decreased. Addition of 7, 8-dihydroneopterin to oxLDL treated macrophages decreased the concentration of intracellular oxidants. In the presence of oxLDL, 7, 8-dihydroneopterin was oxidised to neopterin showing that the 7, 8-dihydroneopterin was scavenging intracellular oxidants generated in response to the oxLDL. The results show CD36 down regulation does not protect human macrophages form oxLDL cytotoxicity but 7, 8-dihydroneopterin intracellular oxidant scavenging is protective.